Proper practice Of unused medicine disposal: opinions of patients at puskesmas 1 Umbulharjo Yogyakarta - Ana Hidayati; Ela Fadilah Pramsa; Woro Supadmi (Pharmaciana, 2023)
Management of unused medicines needs to be done correctly otherwise it will pose negative impacts on health and environment. The purpose of the study is to find out the opinion of patients and whether there is a relationship between demographic characteristics and opinions about patient's disposal practices of unused drugs. This type of research is an analytical observational with cross sectional approach. The number of samples determined by the Lameshow formula obtained a total sample of 96 patients. The sampling technique was carried out by purposive sampling. The research sample was patients who visited Umbulharjo 1 public health center who met the inclusion criteria within the period of March-June 2022. The research instrument was data collection sheet, and data analysis was completed using the chi-square test. Regarding respondents’ opinions on unused medicine disposal practice, results show that most patients return unused drugs to health workers (46.9%). There is a significant relationship between gender and disposal practice methods namely keeping unused medicine at home (p=0.002) and giving it to the patients’ relatives (p=0.049). In addition, there is a significant relationship between educational history and the method of keeping unused medicine at home (p = 0.000). The conclusion of this study is that many patients return unused drugs to health workers for as many as 45 patients (46.9%). There is a relationship between gender demographic characteristics and educational history with opinions about the practice of unused drug disposal.